A survey of the accounting industry on holdings of cryptocurrencies in Xiamen City, China - Huqin Yan; Kejia Yan; Rakesh Gupta (Journal of Risk and Financial Management, 2022)
This is the first survey conducted in China on the holding of cryptocurrencies. Although cryptocurrencies have existed in the world for more than a decade, because the exchange of cryptocurrencies is banned in China, there is no guidance on the holding of cryptocurrencies in China's accounting standards. Moreover, although the exchange of cryptocurrencies is prohibited by the Chinese government, holdings of cryptocurrencies by Chinese entities and individuals cannot be prevented. Thus, we conducted a survey in investors' attitudes towards cryptocurrencies in Xiamen City, a special economic zone (SEZ) and a pilot free trade zone (FTZ) in China. The survey respondents commonly defined cryptocurrencies as investments (45%), inventories (19%), and intangible assets (36%). A total of 84% of respondents stated that the value of a cryptocurrency should be represented by a fair value. These results are similar to those obtained in a survey by The Digital Assets Accounting Consortium (DAAC), but different to the tentative agenda decision of the International Financial Reporting Standards Interpretations Committee (IFRSIC). Additionally, 65% of respondents stated that they prefer to accept cryptocurrencies as cash equivalent currencies, and these cash equivalent currencies were considered to have two main functions: a medium of exchange (56%) and a monetary unit for pricing goods and services (52%).
Keywords: 650; financial reporting standards interpretations committee; survey of cryptocurrencies